Symptoms in the mind : an introduction to descriptive psychopathology - Sims, Andrew C.P (Saunders, 2003)
The 3rd Edition continues to provide a concise and comprehensive introduction to descriptive psychopathology - the basis of clinical psychiatry. New developments in this area, in particular in neuro-imaging, have resulted in the linking of psychopathological symptoms to specific brain changes and these findings are included in the book. In addition there is increased coverage of the controversial area of multiple personality syndrome.
Keywords: Mental Disorders; psychopatologie; duševní poruchy; zdravotně postižení; psychiatrie; Psychopathology